Plasma extracellular vesicle neurofilament light chain as the biomarkers of the progression of Parkinson’s disease - Chien-Tai Hong; Chen‐Chih Chung; Yi-Chen Hsieh; Lung Chan (Biomolecules & Biomedicine)
Parkinson’s disease (PD) is a common neurodegenerative disorder characterized by progressive symptoms, underscoring the urgent need for predictive blood biomarkers. Plasma extracellular vesicles (EVs) offer a promising platform for biomarker development, with neurofilament light chain (NfL) emerging as a potential candidate for neurological diseases. This study evaluated plasma EV NfL as a biomarker for disease progression in a PD cohort.A total of 55 patients with PD (PwP) and 58 healthy controls (HCs) were followed, with PwP completing an average of 3.96 visits and HCs 2.25 visits. Plasma EVs were isolated and validated, and EV NfL levels were measured using an immunomagnetic reduction assay. Generalized estimating equations and Spearman correlations assessed relationships between clinical symptom progression and biomarkers. Although no significant differences in plasma EV NfL levels were observed between PwP and HCs over time, changes in plasma EV NfL significantly correlated with motor symptom progression, specifically with adjusted-total and akinetic-rigidity subscores of the Unified PD Rating Scale (UPDRS) Part III. Additionally, changes in UPDRS Part II scores were significantly associated with plasma EV NfL levels. These findings suggest that plasma EV NfL reflects motor symptom progression in PwP, highlighting its potential as a valuable biomarker for monitoring disease progression and guiding clinical trials in PD.